2010
DOI: 10.1002/dvdy.22261
|View full text |Cite
|
Sign up to set email alerts
|

Differential time course of FSH/FSH receptor complex endocytosis within sertoli and germ cells during rat testis development

Abstract: Follicle-stimulating hormone (FSH) is required for initiation and maintenance of spermatogenesis, a dynamic process of cell proliferation and maturation. By using FSH-gold particles and pulse-chase experiments, we analyzed the kinetics of FSH endocytosis in Sertoli and germ cells during development. Ultrastructural time-dependent analysis demonstrates that FSH was first located on plasma membrane, before being accumulated within the endosomal compartment, in the early endosomes, identified by morphological cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In mammals, the initiation and maintenance of gametogenesis depends not only on the rhythmic variation of sex hormones but also on the dynamic expression of hormone receptors on the germ cell membrane. RAB5A plays an indispensable role in the dynamic recycling of hormone receptors between the cell membrane and cytoplasm (Segretain et al 2010). RAB5A-regulated transport of the LH receptor from the cell surface and its subsequent lysosomal degradation may be associated with dynamic regulation of LH receptor expression during the ovarian cycle by permitting the entry of newly synthesized receptors to the cell surface (Gulappa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the initiation and maintenance of gametogenesis depends not only on the rhythmic variation of sex hormones but also on the dynamic expression of hormone receptors on the germ cell membrane. RAB5A plays an indispensable role in the dynamic recycling of hormone receptors between the cell membrane and cytoplasm (Segretain et al 2010). RAB5A-regulated transport of the LH receptor from the cell surface and its subsequent lysosomal degradation may be associated with dynamic regulation of LH receptor expression during the ovarian cycle by permitting the entry of newly synthesized receptors to the cell surface (Gulappa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Leydig cells, LH receptors are routed to lysosomes where both hormone and receptor are degraded, whereas in Sertoli cells, internalized FSH/FSH receptor complexes are internalized into endosomes and subsequently recycled whole back to the cell surface [27]. Although previously thought to be only expressed by Sertoli cells, recent evidence has found that FSH receptors are also found on spermatogonia, where they also undergo similar receptor internalization and recycling [28].…”
Section: Microscopic and Ultrastructural Testicular Anatomymentioning
confidence: 97%
“…Receptors for FSH are found specifically on the testicular vasculature as well as on Sertoli cells and spermatogonia. 8 We have shown NP conjugation to a rationally selected portion of FSH increased uptake by and protection of Sertoli cells from oxidative stress. 9 The objective of this study is to evaluate the efficacy of anatomic targeting and ligand targeting for the delivery of NPs to testicular tissue in vivo.…”
Section: Introductionmentioning
confidence: 99%